Analisis Faktor Kompetensi Pedagogik Guru Dalam Proses Pembelajaran Menggunakan Algoritma C45 - Ingkana Devi Cahaya; Heru Satria Tambunan; Harly Okprana (LPPM STIKOM Tunas Bangsa, 2021)
Pedadogic competencies are the competencies that teachers must have in managing learning so that the process can run well. Mining data is a series of processes to explore the added value obtained from information or knowledge that can form a decision pattern that will later be used in analyzing pedagogical competency factors the teacher in the learning process for one semester is based on the criteria of understanding students, designing learning, evaluating learning outcomes, learning that educates and dialogues and develops students to share their potential. Pedagogic assessment is done by summing the value of each criterion and using a standard value to determine the final value. The application of the c45 algorithm can be used to prodece a decission tree that will be taken to determine the form of rules or rules that will be used as a decision tree